Evaluasi Pelayanan Penumpang (Studi Kasus: Pelabuhan Dili Timor Leste) - Ni Luh Made Ayu Mirayani Pradnyadari; I Wayan Gede Darma Yoga; Julia Maria Granadeiro Goncalves (Reinforcement Review in Civil Engineering Studies and Management, 2022)
Timor-Leste as a new country has various efforts to advance the country itself, one of which is the achievement is to build several ports in three locations, because for the time being it still mandates one port located in the center of Dili city, namely; "Porto Dili", (port of Dili). Porto Dili port has 2 docks, passenger docks and container docks, facilities at Porto Dili port are inadequate such as the absence of counters for passenger tickets, waiting rooms, passenger toilets and one of the docks has a dual function, namely the loading and unloading of containers and as a passenger dock, this research is expected to realize good service quality in accordance with the needs and desires of its customers which leads to customer satisfaction. This study uses the Costumer Satisfaction Index (CSI) method The satisfactory CSI value is 80% while based on the results of research conducted in porto dili passenger terminal get a CSI value is 26%, this shows if the service on sea public transportation in porto dili port is not good and has not satisfied passengers.